1994
DOI: 10.1152/ajpcell.1994.266.2.c367
|View full text |Cite
|
Sign up to set email alerts
|

Human kidney proximal tubules are the main source of plasma glutathione peroxidase

Abstract: The sites of synthesis of extracellular (E) glutathione peroxidase (GPX), a unique selenoglycoprotein present in plasma, are not known. To investigate the possibility that the kidney is the main source for the plasma GPX, we examined GPX activities and selenium concentrations in the plasma of patients with renal failure on dialysis and nephrectomized patients before and after kidney transplantation. Plasma GPX activities in these patients were 42, 22, and 180% of normal EGPX activity, respectively, whereas pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
204
1
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(221 citation statements)
references
References 25 publications
13
204
1
3
Order By: Relevance
“…The glutathione peroxidase family has at least four member enzymes, but little is known about their physiological function. Extracellular glutathione peroxidase is the predominant form in plasma and is mainly produced in the kidney (Avissar et al, 1989;Huang & A Ê kesson, 1993;Avissar et al, 1994;Huang, 1996), and it is also found in milk (Avissar et al, 1991) and aqueous humor (Huang et al, 1997). It is also the major 75 Se-substituted protein secreted by human thyrocytes incubated with ( 75 Se)selenite, and it was hypothesized that it may be a regulator of thyroid hormone synthesis (Howie et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The glutathione peroxidase family has at least four member enzymes, but little is known about their physiological function. Extracellular glutathione peroxidase is the predominant form in plasma and is mainly produced in the kidney (Avissar et al, 1989;Huang & A Ê kesson, 1993;Avissar et al, 1994;Huang, 1996), and it is also found in milk (Avissar et al, 1991) and aqueous humor (Huang et al, 1997). It is also the major 75 Se-substituted protein secreted by human thyrocytes incubated with ( 75 Se)selenite, and it was hypothesized that it may be a regulator of thyroid hormone synthesis (Howie et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma GPx activity is largely derived from the renal tubular epithelium (19). Both plasma and erythrocyte GPx activity change in relation to the evolution of renal disease (20 -22).…”
Section: Statisticsmentioning
confidence: 99%
“…16 Insignificant reduction levels of GSH-px were determined in patients on HD when compared with control group (p = 0.456) and in patients on CAPD when compared with HD (p = 0.425). Although contradictious results are present, most of other studies support our data.…”
Section: Discussionmentioning
confidence: 93%
“…[22][23][24][25][26] Antioxidant defense systems are less affected in patients on peritoneal dialysis than HD. [15][16][17] This is related to less frequent presence of anemia and moderate amount of lipid peroxidation. 23 Similarly, levels of SOD enzyme were significantly lower in patients on CAPD than HD.…”
Section: Discussionmentioning
confidence: 99%